Computed Tomography Criteria for Differential Evaluation of True and False Lumens in Aortic Dissection - R. S. Muslimov; I. E. Popova; L. T. Khamidova; V. S. Selyaev; I. V. Vasilyeva; L. S. Kokov (Неотложная медицинская помощь, 2022)
The aim of study Based on computed tomography data, to determine the most characteristic criteria for true lumen (TL) and false lumen (FL) in aortic dissection. To identify the relationship of the studied features with the stage of aortic dissection.Materials of the study Computed tomography (CT) data of 115 patients diagnosed with aortic dissection (AD) who were treated at the N.V. Sklifosovsky Research Institute for Emergency Medicine were analyzed. The average age of the patients was 54.5 years (median — 56 years), men predominated in the studied group. AD types according to the De Bakey classification were distributed as follows: Type I — in 47% of patients, Type II — in 16.5%, Type III — in 36.5%. Dissection in the acute stage occurred in 62% of the patient, in the subacute — in 16%, in the chronic — 22%.Results In the studied group, FL in all cases prevailed over the TL by size, regardless of the stage and type of AD. Analysis of lumen ratio showed that in 63.55% of patients, FL occupied 75% or more of the aortic cross-sectional area. Location of FL: at the level of the ascending aorta, along the right and anterior walls of the aorta — 94.5%; in the descending thoracic aorta, along the posterior and left walls — 84%; in the abdominal aorta, along the posterior and left walls — 70%. Calcifications of the non- dissected part of the aortic wall, as a sign of a true lumen, were found in 59.1%. There was no correlation between calcification and the AD stage. Partial thrombosis of one of the lumens was detected in 59% (in FL — 85%, in TL — 13%, thrombosis of both lumens — 2%). The beak signs occurred in 85% of patients with AD, however, it was significantly more often detected in patients with acute and subacute AD stages than in the chronic stage (p<0.001). The cobweb sign was found in one third of patients with AD, however, it was statistically significantly more often determined in patients in acute and subacute stages (p<0.05).Conclusion CT is reasonably considered a highly informative method of diagnosing AD. The signs of true and false lumen presented in the work, as well as their combination, make it possible to perform a quick and error-free marking of the aortic lumen with a high degree of probability. A number of the described CT signs correlate with the stage of AD.